Prevention of deep vein thrombosis in patients undergoing plastic surgery - Torres, Caio de Moura; Ramos, Luisa Natália Rezende; Lopes, João Pedro Garcia Cunha; Souza, Nicole Gundim de; Filho, Adiel Sant'Ana; Sá, Pedro Augusto Tavares de; Antonio , Haroldo Neto Diniz; Filho, Humberto Renato de Oliveira; Torres, Káliston de Moura; Carmo, Clara Barreto Moraes do; Pereira, Millena Batistela; Matozinho, Darah Vitória Paiva (Seven Editora, 2024)
INTRODUCTION: Plastic surgery is the branch of medicine that aims to recover, restore or alter the physical presentation of the patient. It is the medicine of self-esteem and seeks to repair both the physical and the psychological of those who seek it. To this end, the individual undergoes delicate procedures that can lead to complications and possible death. A complication of high incidence and morbidity and mortality is deep vein thrombosis (DVT), which is characterized by the formation of a thrombus (clot) within the lumen of one of the blood vessels of the deep venous system, in any region of the body, but more frequently in the lower limbs. As plastic surgery is classified as elective and for the well-being of the patient, it is of paramount importance that safety in its performance is a priority and listing methods to prevent DVT is one of the ways to seek this safe procedure. OBJECTIVE: This study aims to analyze articles that propose methods to prevent deep vein thrombosis after plastic surgery, in order to understand the usefulness and feasibility of DVT prophylaxis in plastic procedures and to enable the improvement of the surgical technique and the patient's procedure aiming at better recovery and quality of life in the postoperative period. METHOD: To compose this integrative literature review, we used articles obtained from searches in the virtual databases (PubMed, SCIELO and Google Scholar), using the Science and Health Descriptors (DeCS) "Deep Vein Thrombosis"; "Plastic Surgery" and "Prevention", between 2010 and 2021. RESULTS: From the integrative review of the articles, it was evident that there are still many controversies among the authors about the practice of prevention of DVT after plastic surgery. It is worth noting that some authors state that healthy patients without comorbidities do not need to be enrolled in DVT prophylaxis. Even so, there are studies that highlight the high incidence of DVT in patients undergoing plastic procedures, especially in surgical processes that have determinants, such as duration of more than two hours, combined surgeries, type of decubitus and procedure. In this sense, some authors indicate the use of chemoprophylactic drugs, such as Enoxaparin and Rivaroxaban, for patients undergoing such procedures and those with comorbidities, in order to preserve the patient's health. In general, it is attested by the articles that, when well indicated, prophylaxis for DVT in plastic surgery has an efficacy close to 100%. This fact reaffirms the importance and need to develop and expand scientific knowledge in the area. CONCLUSION: Thus, it is possible to conclude that thromboprophylaxis is feasible and useful. However, it must be well indicated and developed, respecting the individuality of each patient by taking into account the individual's health status and the particularities of the proposed plastic surgery procedure. DOI:https://doi.org/10.56238/sevened2023.007-058